PENERAPAN MODEL PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 158 PEKANBARU - Juni Ani Simanjuntak; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on a problem that found in grade VB SDN 158 Pekanbaru class the result of low learning student, it is seen on student’s score in reaching KKM (Maximum Criterion) only 11 people (40,74%) from 27 students. While the school established KKM is 70, then many students who have not reached KKM are 16 (59.26%). Based on these problems it is necessary to apply the interactive learning model in order to help improve student learning outcomes. The interactive learning model is a model designed to get children to ask questions and find answers to their own questions. If the learning takes place actively, it is expected that students can dare to express their opinions and ideas and can affect students learning outcomes. The purpose of this study is to improve the learning outcomes of science students VB grade SDN 158 Pekanbaru. This research was conducted in 2 cycles, which in cycle I consisted of 2 meetings and cycle II consisted of 3 meetings. The data collected in this research is teacher activity data, student activity and test result of student learning in daily test in every cycle. In the first cycle, the teacher activity increased by 70% (enough) and 75% (enough) then in cycle II 80% (good), 85% (good) and 90% (very good). It also occurs in student activity with the percentage gain in cycle I 65% (enough) and 70% (enough) then in cycle II 80% (good), 85% (good) and 90% (very good). In addition to teacher and student activity, students' science learning outcomes also experienced an increase in the average base score of 59.07 with a percentage of 40.47% completeness increased in the first cycle of 22.38% to 72.29 with a percentage of 66.67% . Then on the second cycle, increased by 46.45% from the base score to 86.51 with the percentage of 88.89% completeness. It can be conclude that the implementation of interactive learning model can improve the study result of sains subject of the class VB of elementary SDN 158 Pekanbaru.Keywords: Interactive Learning Model, Learning Result of the Sains